Videoanruf skype: platform pembelajaran digital keterampilan berbicara bahasa jerman siswa sma - Wijayati, Primardiana Hermilia; Novitasari, Anggi (Fakultas Sastra Universitas Negeri Malang, 2022)
This research aimed to describe the ability of students in speaking skills using the Videoanruf Skype platform. This research method used descriptive-quantitative. Data were collected in the form of project-based assignments with the research subjects of class XII students in the first semester from SMAN 5 Malang, SMAN 7 Malang, and SMAN Taruna Nala East Java. The results of students' speaking ability were assessed by two raters. To measure the reliability of students' abilities, the results were analyzed by Rater Cohen's Kappa. The results show that students can develop a dialogue by using the vocabulary in the items well so that the assessment components can be fulfilled properly. However, there is a weakness of the Skype platform, namely that it requires a stable internet network.